2020
DOI: 10.5539/ibr.v13n2p74
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the Relationship Between Supply Chain Management Activities and Operational Performance: Testing the Mediating Role of Strategic Agility-A Practical Study on the Pharmaceutical Companies

Abstract: This study has been conducted to investigate the relationship between the supply chain management (SCM) activities and operational performance through testing the mediating factor strategic agility in (16) pharmaceutical companies listed on Amman stock exchange in Jordan Which is considered one of the most important industrial sectors, where the nature of the work and the problems faced in the performance of supply chain were identified the reasons for the delay of the logistical orders of raw materials they n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A study conducted in [32] found that supply chain management (SCM) activities have a positive impact on operational performance, but this impact is mediated by strategic agility. This means that strategic agility plays a role in translating the benefits of SCM activities into improved operational performance.…”
mentioning
confidence: 99%
“…A study conducted in [32] found that supply chain management (SCM) activities have a positive impact on operational performance, but this impact is mediated by strategic agility. This means that strategic agility plays a role in translating the benefits of SCM activities into improved operational performance.…”
mentioning
confidence: 99%